Research on Reactive Voltage Control of Distribution Network with Distributed Photovoltaic Sources. Issue 1 (1st October 2022) - Chen, Shuhao; Yuan, Ting; Lin, Fei
Abstract: Aiming at the problem that the voltage of multiple nodes exceeds the limit after the distributed photovoltaic source is connected, a reactive voltage control method of distribution network is proposed. It modeled the distribution network system with distributed photovoltaic sources, determined the maximum photovoltaic output and adjustable amount, and calculated the power flow. The line loss can be obtained from the node voltage and rated power, and the power distribution of each branch of the whole network can be further obtained. This paper analyzed the influence of photovoltaic power access on the voltage quality of the distribution network from the perspective of power. It calculated the reactive output power of reactive power compensation equipment of upstream and downstream nodes. In this paper, the active power of distributed generation is locally reduced at each out-of-limit node to control the voltage. The experimental results show that the proposed method can effectively improve the relationship between photovoltaic output and voltage, and realize the correction of photovoltaic regulation. Therefore, it can reduce the risk of voltage out of limit and improve the voltage quality.